BUNYI HAND PHONE DALAM PERSPEKTIF HADIS - Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Today mobile is a loyal companion for people in activities, not least when performing prayer services. The performance of prayer requires tranquility and revelation, but if suddenly the hand phone rings when the owner is praying, then the calmness and solitude will dissolve which has implications for the cancellation of the prayer. Because the issue of mobile phones did not exist at the time of the Prophet, the hadith used was the narrative of Abu Hurairah who explained that canceling one's prayer is due to women, donkeys and dogs. Based on the results of the validity test of both the traditions and matrices of these traditions, the quality is valid. When viewed from an anthropological perspective, women have an attraction, donkeys have an annoying voice, while black dogs are frightening. If the hadith is understood contextually and substantively, then anything that has attraction then is in front of people who are praying will disturb and affect the prayer's prayer, as well as what sounds suddenly ring in the middle of the execution of the prayer will interfere with the prayers of the owner. If a woman is symbolized as an attraction, the donkey's voice is symbolized as disturbing her husband's behavior and the dog is symbolized by fear, so that one's prayer is nullified, if all three are crushed by the sound of a cellphone, then the sound of the cellphone can cancel the prayer.